1999
DOI: 10.1063/1.369541
|View full text |Cite
|
Sign up to set email alerts
|

Fresnoite: A new ferroelectric mineral

Abstract: Fresnoite, Ba2TiOSi2O7, has been predicted structurally to be a new ferroelectric. Detection of both ac and dc dielectric hysteresis verifies the prediction. The spontaneous polarization Ps estimated from the hysteresis at 1.2 MV m−1 ac is ∼0.2 C m−2 at 295 K, comparable with the minimum Ps observed in one-dimensional ferroelectrics. A reproducible calorimetric anomaly with entropy change 0.19(3) J mol−1 K−1 at 433(2) K in polycrystalline material coincides with a small dielectric and pyroelectric anomaly prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…16 In addition, Takahashi et al reported that the fresnoite-type phases showed large second-order optical nonlinearities comparable to that of LiNbO 3 single crystal.…”
Section: Introductionmentioning
confidence: 99%
“…16 In addition, Takahashi et al reported that the fresnoite-type phases showed large second-order optical nonlinearities comparable to that of LiNbO 3 single crystal.…”
Section: Introductionmentioning
confidence: 99%
“…It is surprising that the ceramic samples fail to reveal the dielectric anomaly shown in case of single crystal at 433 K [3]. Not only that, but a small reproducible dielectric anomaly has also been reported in the frequency range 0.1-100 kHz at 805 K. However, the single crystal X-ray data taken at 297 K and 573 K revealed no change in symmetry except small changes in atomic position, the largest of which were less than 0.02Å [8]. Recent studies on oriented crystallization using thermal gradient, crystallization kinetics, and electrical properties through impedance spectroscopy were also carried out on fresnoite and fresnoite like glassy materials [9][10][11].…”
Section: Introductionmentioning
confidence: 84%
“…The mineral shows a noncentrosymmetric tetragonal crystal structure with space group P4bm [2]. Due to its noncentrosymmetricity, the material shows good ferroelectric, piezoelectric, pyroelectric, optical, and other physical properties useful for different practical devices [3][4][5][6][7][8]. The single crystal data of fresnoite shows a broad peak in dielectric permittivity at ∼433 K but the same peak is absent in dielectric loss curve.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that the differential scanning calorimetry (DSC) measurement from 300 to 875 K showed a wide ($60 K) reproducible thermal anomaly at 433 K with enthalpy change DH = 60(10) J mol À1 and corresponding entropy change DS = 0.19137 J mol À1 K À1 . A thermal anomaly of comparable width was also observed at 810(5) K with DH = 160 J mol À1 and DS = 0.2 J mol À1 K À1 [13]. Uchida et al suggested that the second order optical nonlinearity of the crystal was strongly affected by the distortion of the crystal structure [15].…”
Section: Introductionmentioning
confidence: 86%
“…It is surprising that the ceramic samples fail to reveal a reproducible dielectric anomaly at 433 K shown in case of single crystal [4]. Not only that a small reproducible dielectric anomaly has also been reported in the frequency range 0.1-100 kHz at 805 K [13]. It was reported that an elastic anomaly observed at 435 K might likely be associated with a commensurate-incommensurate phase transition [14].…”
Section: Introductionmentioning
confidence: 88%